Comparative Clinical Audit of Neurosurgical Procedures Across Three Institutions: A Multi-Center Retrospective Study (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Institutional audits are essential in neurosurgery to evaluate the quality of care, identify gaps, and guide improvements. Comparing multiple centers provides a broader understanding of practice patterns and outcomes.Methods: This is a multi-center retrospective review of neurosurgical procedures performed at Shaheed Suhrawardy Medical College Hospital (ShSMCH), Popular Medical College Hospital (PMCH), Dhaka and Pranto Specialized Hospital (PSH), Mymensingh over Jan 2022- Dec 2024. Key variables including case volume, procedure types, outcomes, and complication rates were analyzed.Results: A total of 530 cases were analyzed: ShSMCH (200), PMCH (180), and PSH (150). The mortality rates were 5%, 1%, and 0.6% respectively, while complication rates were 14%, 3%, and 5%. The most common procedures were Fenestration & Discectomy, Spinal Stabilization, ACDF, Brain Tumor Excision, VP shunt and Trauma Craniotomy.Conclusion: This study highlights institutional variations in neurosurgical practice and outcomes, indicating the need for standardized care protocols and quality improvement initiatives.J Shaheed Suhrawardy Med Coll 2024; 16(2): 49-52